For a sociology of social change. Consideraions on the sociologist's work - Bagnasco, Arnaldo (Sociología del Trabajo, 2022)
The article proposes a brief enrichment of the vicende economiche e sociali negli anni di Sociologia del Trabajo. The first paragraph is a subject of economic change, elaborated from the point of view of economic sociology, it is worth saying with reference to the institutional assets that have regulated the interaction of interest in gioco in successivi moment; The second paragraph proves to render an account of how the company has changed in that process, showing the evolution of its structure with reference to its social distancing.The last part is a review of the type of sociology useful to practice now, in the change described above. With the knowledge of all the references available in a vast literature of research, close to segnavia or indizi, I propose a journey in the direction of a rational sociology, it is worth saying a sociology that has a sense of the measurement, is realistic, reformist, impegnant. In a moment when I am aware of the institutional withdrawal, I am responsible for sociology and will collaborate in the strengthening and innovation of the democratic institutions that have been built, and I will contribute, for the part, to the joint asset project for regulation in the change.
Keywords: Sociology of work; democratic institutions; social inequality